DOI: 10.14264/uql.2018.759
|View full text |Cite
|
Sign up to set email alerts
|

Weather variability and coconut production in Sri Lanka: state-contingent analysis

Abstract: Weather variability presents an external impediment that increases the uncertainty in crop production potential specially for perennial crops under rain-fed cultivation. In particular, increasing rainfall variability that has accompany climate change in the tropics is increasing production uncertainty exposing farmers to a range of risks. Producer behavior under uncertainty is theoretically advanced in Chambers and Quiggin (2000) with the development of the state-contingent approach. This theory advocates farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…Given the situation, the major challenge the coconut industry is facing at present is to increase the national production to cater to the growing demand of these two sub-sectors. Hence, overcoming the relative profitability of coconut production and increasing the surplus availability of coconuts for kernel-based processing industries have become important policy issues for Sri Lanka (Jayalath, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the situation, the major challenge the coconut industry is facing at present is to increase the national production to cater to the growing demand of these two sub-sectors. Hence, overcoming the relative profitability of coconut production and increasing the surplus availability of coconuts for kernel-based processing industries have become important policy issues for Sri Lanka (Jayalath, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, coconut production is significantly associated with the land suitability class of coconut and the uses of recommended practices, when other biotic factors are non-limiting (Somasiri et al, 1994;Peries et al, 2001). Jayalath (2018) has estimated an empirical model based on the state-contingent production function, to examine how farmers manage coconut production uncertainty under different states of nature. Results revealed that the existing commercial production systems represent a set of flexible farming technologies which allows farm managers to better manage uncertain wet and dry states of nature.…”
Section: Introductionmentioning
confidence: 99%